Impacts of CA9 gene polymorphisms on urothelial cell carcinoma susceptibility and clinicopathologic characteristics in Taiwan. - Shian-Shiang Wang; Yu-Fan Liu; Yen-Chuan Ou; Chuan-Shu Chen; Jian-Ri Li; Shun-Fa Yang (PLoS ONE, 2013)
Carbonic anhydrase 9 (CA9) is reportedly overexpressed in several types of carcinomas and is generally considered a marker of malignancy. The current study explored the effect of CA9 gene polymorphisms on the susceptibility of developing urothelial cell carcinoma (UCC) and the clinicopathological status.A total of 442 participants, including 221 healthy people and 221 patients with UCC, were recruited for this study. Four single-nucleotide polymorphisms (SNPs) of the CA9 gene were assessed by a real-time PCR with the TaqMan assay. After adjusting for other co-variants, the individuals carrying at least one A allele at CA9 rs1048638 had a 2.303-fold risk of developing UCC than did wild-type (CC) carriers. Furthermore, UCC patients who carried at least one A allele at rs1048638 had a higher invasive stage risk (p< 0.05) than did patients carrying the wild-type allele. Moreover, among the UCC patients with smoker, people with at least one A allele of CA9 polymorphisms (rs1048638) had a 4.75-fold (95% CI = 1.204-18.746) increased risk of invasive cancer.The rs1048638 polymorphic genotypes of CA9 might contribute to the prediction of susceptibility to and pathological development of UCC. This is the first study to provide insight into risk factors associated with CA9 variants in carcinogenesis of UCC in Taiwan.